Evaluation of Interleukin-22 and Toll-like receptor-2 as an Immunological Biomarkers in Breast Cancer Patients - Al-Hasso, Ikram Khazal Qasim (AL-Kindy College Medical Journal, 2024)
Background: Interleukin-22 is an effector cytokine belongs to the IL-10 family. Signaling of this cytokine control tumor development by boosting cancerous cells growth. Toll-like receptor-2 act key function in activation of tumor cell proliferation besides increasing tumor cell invasion.Objectives: to assess the level and reliability of IL-22 and TLR-2 in patients with breast cancer as a particular diagnostic and prognostic biomarkers in these patientsSubjects and Methods: Ninety breast cancer and sixty healthy control women participated in the current study. ELISA was utilized to measure IL-22 and TLR-2 in the serum of all participating individuals.Results: The results revealed a significantly higher IL-22 concentrations in patients with breast cancer compared to controls (169.1±43.6 ng/L vs. 82.1±19.5 ng/L (P = 0.010)).Patients in Stage-IV and Grades -2 and -3 demonstrated elevated IL-22 concentrations (239±65.1 ng/L besides 201.2±36 ng/L and 321.2±62.6 ng/L respectively), while there is no significant differences in the concentrations of TLR-2 between patients (for different stages and grades)  and control (39.1±11.2 ng/ml vs. 32.3±10.7 ng/ml (P = 0.062).Conclusions: Increased serum concentrations of IL-22 in patients with breast cancer with higher concentration in advanced stages. This might confirm a potential value of this cytokine as a marker in the pathogenesis of the disease and its promising role as new diagnostic tools of this cancer. TLR-2 shows non-significant difference in the concentration in patients with breast cancer as compared to control group.